Penggunaan Media Gambar Untuk Meningkatkan Hasil Belajar Matematika Siswa Pada Pembelajaran Tematik Tema Peristiwa Kelas I A Di SD Negeri 002 Rambah T.P 2014/2015 - Hardawati Hardawati (JURNAL PENDIDIKAN ROKANIA, 2018)
This research is action research. This study aims to find out the results of learning Matematics class I A SD Negeri 002 Rambah as many as 28 people consisting of 12 men and 16 women. The focus of this research is the learning by using the media picture to increase the learning outcomes in the students of grade IA SD Negeri 002 Rambah. The media picture proved to improve student learning outcomes from the average mastery learning students before 50% improvement, cycle I 78.6%, just achieved mastery classically in cycle II of 92.9%. The average student's activity cycle I is 62,5. In the second cycle increased to 84.3. Activity of teachers has an average increase in cycle I 85. Cycle II average 100. From the results of the study can be concluded that the use of media picture can improve student learning outcomes on thematic learning the theme of Class IA events in SD Negeri 002 Rambah Lesson Year 2014/2015